THE CONSTITUTIONAL COURT AND THE REPERCUSSION OF ITS PROCEDURAL AUTONOMY ON DEMOCRACY IN THE CONSTITUTIONAL STATE OF LAW - Rojas Ameghino, Cristhian Angelo (2026)
This article critically analyzes the procedural autonomy of the Peruvian Constitutional Court as the power to create procedural rules through jurisprudence and binding precedents, intended to fill legal gaps and guarantee the protection of fundamental rights. It argues that, in certain cases, the Court's exercise of this power has exceeded the role of a negative legislator, assuming the powers of the Legislative Branch by creating procedural institutions not provided for by law. This constitutes judicial activism and undermines legal certainty and the separation of powers. Based on a doctrinal, jurisprudential, and comparative analysis, the article proposes establishing formal and substantive limits to preserve constitutional supremacy and institutional balance.